Effect of Health Education on Knowledge About Stunting Among The Community in Teluk Sasah District of Bintan Island, Riau Island, Indonesia - Athiyyah, Alpha Fardah; Nur Aisiyah Widjaja; Suminar, Dewi Retno; Cahyanti, Ika Yuniar; Sulistiawati (Journal of Community Medicine and Public Health Research, 2025)
Stunting in early life, particularly in the first 1000 days has longterm consequences on children’s physical growth, cognitive performance, and emotional well-being. Adequate parental and community knowledge plays a critical role in enabling early recognition, prevention, and appropriate management of factors contributing to stunting. This study aims to investigate the impact of health education on community knowledge related to stunting. A cross-sectional design was applied involving 24 adult participants (≥ 18 years) from the general public in Teluk Sasah District, Bintan Island using total sampling. The educational intervention was delivered through pamphlet distribution, health talks, and discussions with experts focusing on stunting. Pre and post-test were conducted to assess their understanding about stunting. Data were analyzed using Statistical Product and Service Solution (SPSS) Software version 16.0, employing the Shapiro-wilk for normality and the Wilcoxon signed-rank test to compare scores before and after the interventions. This study demonstrated a significant difference between pre-test and posttest (80.83 ± 9.74 vs 90.83 ± 7.76, p=0.000). Furthermore, the minimum score of post-test and pre-test also improved markedly (60.00 vs 70.00, p=0.000). This study found that the implementation of health education, including pamphlet distribution, classical lectures, and case discussions, effectively enhanced participants’ knowledge about stunting.